On the Construction of Phenomenological Coronal Mass Ejection Models - D. V. Peregoudov (Space Weather)
Abstract We consider recently developed 3DCORE coronal mass ejection (CME) model. We find that the magnetic field of 3DCORE violates both Maxwellian equations: the one for absence of magnetic monopoles and the other one for Faraday induction (“frozen‐in” condition). We recall basic heliospheric magnetohydrodynamical equations and show that they lead to a number of conservation laws. These conservation laws should be taken into account when developing a phenomenological CME model. We show that conservation laws take extremely simple form when written in Lagrange coordinates frozen into plasma. Thus, these are easy to conform and practically, there are no reasons not to conform them. We propose a modification of 3DCORE magnetic field that satisfies Maxwellian equations.